Smisli hrepenenja - Snoj, Vid (Primerjalna književnost, 2000)
Senses of Yearning: Ivan Cankar's literature and the New Testament's christianity. - The main topic of Ivan Cankar's literature is that of human yearning. The discussion, however, starts with the definition of the sense of the yearning in the New Testament. As God, according to St. Paul, "raises the dead" and "calls into existence non-beings as beings", yearning follows this call, ignoring the division between the living and the dead which the world respects, and has a para-ontological sense. In Cankar's work this para-ontological or, even more, meta-ontological determination of yearning which has developed in subsequent Christian literature is lost, and yearning is identified with the basic feeling of the schöne Seele, as Hegel put it, i.e. of the empty subject which does not enter into the reality. It is this very kind of yearning that, similarly to Prešeren's glorification of a woman, has become the paradigm of Slovene literature. Howevwe, this concept of yearning in Cankar's late works is redefined and filled with the sense of New Testament yearning for new life after death.
Keywords: Bible; Cankar, Ivan, 1876-1918; hrepenenje; literarne študije; literarni motivi; Slovene literature; slovenska književnost; Sveto pismo